Temperature controlled NiCd battery charger - Hazer, Mohamad Sayuti (2008)
Nowadays electronic gadgets are widely use due to the growth of new technology. Most electronic gadgets use dry cell as their main energy source; this is due to its small size, efficiencies and recharge ability. Recharge the battery can save cost and reduce the thrown of old battery which can effect the environment. Electrochemical reaction in battery is affected from the temperature. Connecting a device creates a current and the electrons flow through the device to the positive side. At the same time, an electrochemical reaction takes place inside the batteries to replenish the electrons. The effect is a chemical process that creates electrical energy. Once the battery nears a full charge, excess charge current becomes heat. The heat begins to accumulate in the mass of the battery side. As the heat accumulates, temperature of the battery begins to rise. Current through the battery begins to double for every degree Celsius, thus more power is dissipated in the battery which means more heat is generated, as a result more current flows which produce more heat. The heat increase the resistance of the battery, thus the voltage loss occurs and the charging became less efficiency as a result the optimum charging can’t be achieved. To overcome this problem, the cooling fan is added to maintain the battery temperature. The sensor is function to measure the battery’s temperature and driver circuit driving the cooling fan if the battery’s temperature reaches the set value (31 ºC).